Population burden of betel quid abuse and its relation to oral premalignant disorders in south, southeast, and east Asia: an Asian betel-quid consortium study - Lee, Chien-Hung; Min-Shan Ko, Albert; Warnakulasuriya, S.; Ling, Tian-You; Sunarjo, .; Rajapakse, Palandage Sunethra; Zain, R.B.; Ibrahim, Salah Osman; Zhang, Shan-Shan; Wu, H.J.; Liu, Lin; Kuntoro, .; et al. (American Public Health Association, 2012)
Objectives. We investigated the population burden of betel quid abuse and its related impact on oral premalignant disorders (OPDs) in South, Southeast, and East Asia. Methods. The Asian Betel-Quid Consortium conducted a multistage sampling of 8922 representative participants from Taiwan, Mainland China, Malaysia, Indonesia, Nepal, and Sri Lanka. Participants received an interviewer-administered survey and were examined for oral mucosal disorders. Results. The prevalence of betel quid abuse was 0.8 to 46.3 across 6 Asian populations. The abuse frequency was over 40.5 for current chewers, with the highest proportion in Nepalese and Southeast Asian chewers (76.9?99.6). Tobacco-added betel quid conferred higher abuse rates (74.4?99.6) among Malaysian, Indonesian, and Sri Lankan men than did tobacco-free betel quid (21.8?89.1). Gender, lower education level, younger age at chewing initiation, and clustering of familial betel quid use significantly contributed to higher abuse rates. Indonesian betel quid abusers showed the highest prevalence of OPDs and had a greater risk of OPDs than did nonabusers. Conclusions. Betel quid abuse is high in regions of Asia where it is customarily practiced, and such abuse correlates highly with OPDs. By recognizing abuse-associated factors, health policies and preventive frameworks can be effectively constructed to combat these oral preneoplasms.